In-situ measurement of temporal changes in thickness of polymer adsorbed films from lubricant oil by vertical-objective-based ellipsometric microscopy. (January 2022) - Song, Yuxi; Fukuzawa, Kenji; Itoh, Shintaro; Zhang, Hedong; Azuma, Naoki
Abstract: Understanding the formation mechanism and conformation of the adsorbed film formed by additives is critical to clarify the boundary lubrication characteristics. In this study, using the vertical-objective-based ellipsometric microscope (VEM), which can measure nm-gaps between solid surfaces, we proposed a new method for in-situ measuring the thickness of additive adsorbed film in the lubricant oil. In this method, the adsorbed film thickness was measured by measuring the gap between the solids, which was filled by the additive film. The formation process of polyalkylmethacrylate (PAMA) polymer additive adsorbed film was successfully observed. Moreover, we revealed that the PAMA adsorbed films adopted two different conformations depending on the molecular weight and concentration of the polymer: the flattened single-layer conformation and double-layer conformation. Highlights: A new method for in-situ measuring thickness of additive adsorbed film from lubricant oil is proposed. The temporal thickness change of polyalkylmethacrylate (PAMA) adsorbed film during adsorption was observed. Depending on Mw and concentration of PAMA, adsorbed film could adopt flat single-layer or double-layer conformation. The competition between flattening of adsorbed polymers and supplying of polymers from oil decided the conformation.